ChemInform Abstract: Synthesis of 5‐Hydroxy‐Δ1‐pyrrolines from Aryl Isoalkyl Ketoximes and Acetylene in a Tuned Superbase Medium. Issue 46 (27th October 2016) - Shabalin, Dmitrii A.; Dvorko, Marina Yu.; Schmidt, Elena Yu.; Protsuk, Nadezhda I.; Trofimov, Boris A.
Abstract: Title compounds (III) bearing aromatic substituents at the C—N double bond are synthesized in moderate yields by reaction of the corresponding ketoximes (I) and acetylene (II).